Spotted Fever: An Undercover Cause of Hemophagocytic Lymphohistiocytosis in the Immediate Postpartum - Karen Aida Ibarra Stone; Jose Gabriel Solis; Enrique Blanco-Lemus; Jose Malagón-Rangel; Guadalupe Gordillo-Perez (Case Reports in Infectious Diseases)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by a dysregulated activation of the immune system that causes fever, cytopenias, organomegalies, and hemophagocytosis. There are infectious, neoplastic, rheumatologic, and miscellaneous causes. Rickettsioses are a neglected cause of HLH. We report a confirmed case of an immunocompetent woman in Mexico with postpartum HLH secondary to spotted fever. We did a review of the literature for search of similar cases. The association between these two diseases was found in postmortem studies, unrelated to postpartum. This diagnosis should be considered in all patients with HLH without an evident cause in areas of epidemiological risk.